A CASE REPORT ON EFFECTIVE MANAGEMENT OF RETAINED PRODUCT OF CONCEPTION THROUGH AYURVEDA REGIMEN (International Journal of Ayurveda and Pharma Research, 2021)
The term retained products of conception (RPOC) refers to intrauterine tissue that develops after conception and persists after medical and surgical pregnancy termination, miscarriage, and vaginal or cesarean delivery. Approximately half of the conceptions are not even recognized 10- 15% is lost during 1st trimester and additional 2-3% is lost in later pregnancy. The word abortion means expulsion from the uterus of the product of conception before the fetus is viable. This period of viability is different in different views. In modern medicine the period of viability is taken as 7 months. In Ayurveda this abortion is mentioned with the name of Garbhasrava or Garbhapata. A 30 yr old female patient came to NIA opd with a complaint of heavy bleed continously since 1 month. On examination it was found, she has taken MTP pill from local clinic. D and C was done though she was getting her bleed continously. Then, she came to NIA opd for futher management and was given Dashmool Kwatha, Ajmodadi Churna, Triphala Guggulu and Prataplankeshwar ras for 7 days. Then the patient was advised for USG which revealed no retained product of conception.